In vitro propagation of Habenaria hybrids - Sotthikul C. (2017)
To assist a breeding project of terrestrial orchids, in vitro propagation of Habenaria hybrids was performed. A study about the influence of culture vessel and light was carried out by culturing seedlings of an inbred of H. rhodocheila. Two different vessels (16 ounce-round-shaped glass vessel and 13 ounce-square-shaped plastic vessel) were used for micropropagation under various LED light conditions (white, red, blue, red+blue, and red/blue light). After 8 week culture, an interaction between vessel type and light conditions was observed; this affected the number of plantlets, diameter of plantlets, number of leaves, leaf width, number and size of roots but not the height of plantlets or the leaf length. High multiplication rate (1:3) was obtained when cultures were grown in plastic vessels under blue light. Plantlets grown in round-shaped glass vessels under red/blue light formed 5.8 tubers having 0.53 cm in diameter. An experiment on the effects of different types and concentrations of chitosan on growth of another inbred line of H. rhodocheila was also performed. It was found that both type and concentration of chitosan affected the number and size of leaves, height of plantlets, number and length of roots and also sizes of leaf cell and chloroplast. However, the number of plantlets and diameter of roots were not affected.